KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA TABALANSU, PAPUA - Pujiningrum Palimbunga, Ika (JURNAL MASTER PARIWISATA; Volume 05, Nomor 01, July 2018DO - 10.24843/JUMPA.2018.v05.i01.p10, 2018)
Tourism has begun to develop in the village of Tablanusu. The community as a major component in tourism development plays an important role to develop the local potentialities of nature and culture. The purpose of this study is to identify the forms of community participation in tourism development in Tablanusu village. This study uses descriptive qualitative method, the technique of collecting data through observations, interviews and documents study. This study was conducted at the Tablanusu village. Informants in this study were 17 people selected by purposive sampling. This research uses the theory of participation. The results of the study reveal the form of participation in planning, implementation, and monitoring. The research results suggest the government to support the community to improve the quality of human resources, building infrastructures which are still lacking, and make good cooperation between tourism stakeholders including the local community in Tablanusu village.